The "Open Branch" Technique: A New Way to Prevent Paraplegia After Total Endovascular Repair of Thoracoabdominal Aneurysm. Issue 4 (28th December 2015) - Mangialardi, Nicola; Lachat, Mario; Esposito, Andrea; Puippe, Gilberte; Orrico, Matteo; Alberti, Vittorio; Fazzini, Stefano; Ronchey, Sonia
Abstract : Introduction: Staged endovascular treatment of thoracoabdominal aortic aneurysms (TAAA) has been proved to be an effective strategy to reduce the risk of spinal cord ischemia (SCI). Several techniques have been described: some imply the staged coverage of the aorta, other the temporarily perfusion of the sac through a branch left unstented or a dedicated branch that will be occluded later. The aim of those is to facilitate the expansion of the collateral network that perfuses the spinal cord. However, each of them, have some disadvantages such as the need of two interventions of big magnitude and the risk of target vessel occlusion or endograft displacement. We describe a new technique to treat TAAA in a staged manner. Technique: The first step of our technique is the thoracoabdominal endograft deployment with the branching of all target vessels; one of these is branched with a bare stent inside which a covered stent will be placed in a second step, which can be perfomed under local anesthesia. We named this technique "open branch" (OB). Before insertion of the covered stent, a balloon is inflated inside the bare stent to simulate the complete sac exclusion to evaluate eventual neurological complication. Results: Two patients with Crawford type II TAAA and one with a suprarenal aneurysm following the open repair of an infrarenal aortic aneurysm were treated. No cases of SCI were observed after the two procedures. Median interval time between the two procedures was 8, 6 weeks (4–16). Between the two steps, no aneurysm growth or rupture and no branch occlusion or endograft displacement was observed. Conclusions: These three cases of "OB" technique show that this is a safe and feasible alternative strategy to treat TAAA in a staged manner. © 2015 Wiley Periodicals, Inc.